INTEGRASI LITERASI MEDIA DAN INFORMASI DALAM PRAKTIK JURNALISME DI SUMATERA SELATAN - Jufrizal; Adi Wirawan; Dinda Anugerah Tristi; Adriansyah Admaja (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study aims to find out how the methods and level of competence of journalists in South Sumatra in integrating media and information literacy into journalism practices and what are the obstacles faced in implementing it. The research was conducted using a qualitative approach. Data was collected through in-depth interviews, observations, and text analysis. The results of the study show that Palembang Express journalists have a high level of competence (Advanced) in integrating media and information literacy. They have personal competence, Critical Understanding, and good communication, and are constantly undergoing training and experience to improve their abilities. This allows them to produce accurate, balanced, and useful news for the community. The implementation of the integration of media and information literacy in journalism practice is a very important step to ensure high-quality, accurate, and useful news production for the community. Journalists who have strong media and information literacy will be able to understand, analyze, and evaluate information from various media sources, so that they can produce accurate, balanced, and informative news. The obstacles faced by journalists in implementing media and information literacy can be categorized into three, namely: lack of formal training and education, pressure to produce news quickly, and limited access to information sources. These constraints can have a negative impact on the integrity and quality of news produced by journalists. To overcome this, efforts are needed to improve media and information literacy among journalists. These efforts can be made through training, education, and development in the media industry.